Impact of severity of bronchial asthma on oral health in children - Alrashdi, Murad; Alyahya, Abdullah (Frontiers in Oral Health, 2025)
BackgroundThe relationship between asthma and oral health has garnered increasing attention due to overlapping risk factors, such as altered immune responses and behavioral changes.ObjectiveTo assess and compare the oral health status of children with bronchial asthma to their healthy siblings and unrelated healthy controls in the Qassim region, KSA.Materials and methods180 participants were included in the present study and were divided into 3 groups as follows: Group A: 60 children with confirmed diagnosis of long-standing bronchial asthma, group B: 60 healthy subjects who served as a negative control group, group C: 60 healthy siblings of asthmatic children served as a Sibling control group (participants had the same dietary patterns and socioeconomic standards as participants of group A). Dental caries were assessed using the Decayed, Missing, and Filled Teeth (dmft/DMFT) index, which is a standardized and widely used measure of Decayed, Missing, and Filled Teeth in dental epidemiology. Gingival health was evaluated via the Gingival Index (GI).ResultsPost hoc analysis was applied to evaluate the differences between the 3 studied groups regarding DMF score and gingival index and all these differences were found to be highly significant. Patients with bronchial asthma (Group A) were further subdivided into 3 subgroups according to severity of asthma (25 patients had mild asthma, 23 patients had moderate asthma, and 12 patients had severe asthma) based on GINA guidelines. Strikingly, all the differences between these 3 subgroups regarding demographic data, DMF score and gingival index were all insignificant. Further evaluation of each subgroup was done by applying post hoc analysis and each of the 3 subgroups was found to be significantly different than the positive and negative control groups regarding DMF score and gingival index.ConclusionBronchial asthma has direct and indirect effect (related to drug therapy) on oral health. Dealing with some modifiable cofactors could be helpful in improving oral health in children with asthma.